A tubular kaolin modified ammonium polyphosphate functional monomer and preparation method thereof

By embedding ammonium polyphosphate into the tubular kaolin, its water resistance and compatibility are improved, and the problems of poor water resistance and compatibility in the polymer system are solved, achieving efficient and environmentally friendly flame retardant effects.

CN115850799BActive Publication Date: 2025-01-03SHANDONG ACAD OF MARINE CHEM ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211662383.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-01-03
Estimated Expiration
2042-12-23

Smart Images

  • Figure CN115850799B_ABST
    Figure CN115850799B_ABST
Patent Text Reader

Abstract

The invention discloses a tubular kaolin modified ammonium polyphosphate functional monomer, wherein the functional monomer is prepared by mixing nano-SiO 2 The ammonium polyphosphate treated by grafting, epoxy coating or melamine coating is embedded in the tubular kaolin to obtain the obtained product. The functional monomer formed by the organic-inorganic hybrid reaction of ammonium polyphosphate and tubular kaolin maximizes the synergy of the advantages of ammonium polyphosphate and tubular kaolin, significantly improves its water resistance, and greatly improves its carbonization effect and flame retardant efficiency, and can be directly applied to the flame retardant of related materials. The reaction process of the present invention is simple, the raw materials are easily available, the operation is convenient and safe, and it is easy to promote and apply, and has good industrial promotion and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a tubular kaolin modified ammonium polyphosphate functional monomer and a preparation method thereof. Background Art

[0002] With the development of society, polymer materials have been widely used in various fields of production and life. At the same time, most polymer materials are combustible or flammable, which brings potential fire hazards. The flame retardancy of polymer materials themselves has also become an important part of material modification.

[0003] At present, the most commonly used and effective flame retardants for fabrics and plastics are mainly brominated flame retardant systems and P / N halogen-free flame retardant systems. The flame retardant mechanism of brominated flame retardants is mainly gas phase flame retardancy, and the P / N system works by flame retardant carbonization. Regardless of the system, it is likely to produce synergistic effects with ammonium polyphosphate. Ammonium polyphosphate, also known as ammonium polyphosphate or condensed ammonium phosphate (APP for short), has the characteristics of excellent performance, non-toxic and odorless, no generation of corrosive gas, low hygroscopicity, and high thermal stability. It can be widely used in the fields related to flame retardancy of plastics and coatings. Ammonium polyphosphate and brominated flame retardants such as decabromodiphenylethane can have phosphorus-bromine synergy, effectively improving flame retardant efficiency and reducing costs; synergistic effects with suitable carbon sources, gas sources and other related halogen-free flame retardants can form a classic intumescent flame retardant system.

[0004] However, APP also has corresponding disadvantages. As the main acid source of intumescent flame retardants, its application and development are limited by its poor water resistance and poor compatibility with substrates. After long-term storage, the flame retardant will migrate, precipitate or seep out of the polymer system to the polymer surface, resulting in a "white frost" phenomenon and affecting the physical properties of the flame-retarded material. Therefore, effective modification of APP is of great significance to the use and development of intumescent flame retardants. Summary of the invention

[0005] The purpose of the present invention is to provide a new type of modified water-resistant ammonium polyphosphate with a tubular structure, which not only greatly improves water resistance, but also has the advantages of strong thermal stability, halogen-free and environmentally friendly, flame retardant and high efficiency, low toxicity and low smoke, etc. In addition, it has good compatibility with polymer materials. This modified APP can form phosphorus-bromine synergy with brominated flame retardants, and can also be used in classic intumescent flame retardant systems as acid sources and carbon sources.

[0006] To achieve the above object, the tubular kaolin modified ammonium polyphosphate functional monomer provided by the present invention is prepared by embedding ammonium polyphosphate treated by nano-SiO2 grafting modification, epoxy coating modification or melamine coating modification into the interior of tubular kaolin.

[0007] The tubular kaolin modified ammonium polyphosphate functional monomer is prepared by the following steps (1), (2) or (3):

[0008] (1) ammonium polyphosphate and ethanol are mixed evenly, and then silica sol is added dropwise at a temperature of 40-70°C under stirring. After the addition is completed, the reaction is continued for 2-5 hours. After the reaction is completed, tubular kaolin is added and the reaction is continued for 3-5 hours. After the reaction is completed, solid-liquid separation is performed. The separated solid is washed and dried to obtain tubular kaolin modified ammonium polyphosphate functional monomer;

[0009] (2) Mixing melamine and formaldehyde aqueous solution, adjusting the pH to 7-9 with triethanolamine aqueous solution, heating to 60-85°C and reacting for 20-60 minutes, and performing solid-liquid separation after the reaction to obtain melamine-formaldehyde polymer; mixing ammonium polyphosphate and ethanol evenly, adjusting the pH to 4-6 with hydrochloric acid, heating to 70°C-80°C, adding melamine-formaldehyde polymer, keeping the temperature for reaction for 1.5-3h, then adding tubular kaolin, and continuing the keeping temperature for reaction for 3-5h. After the keeping temperature for reaction is completed, performing solid-liquid separation, and washing and drying the separated solid to obtain tubular kaolin modified ammonium polyphosphate functional monomer;

[0010] (3) Mix ammonium polyphosphate and ethanol evenly and adjust the pH to 4-6 with hydrochloric acid, raise the temperature to 70°C-80°C, add epoxy resin, and keep the temperature for reaction for 1.5-3h; after the reaction is completed, add tubular kaolin, and continue to keep the temperature for reaction for 3-5h. After the reaction is completed, perform solid-liquid separation, and wash and dry the separated solid to obtain tubular kaolin modified ammonium polyphosphate functional monomer.

[0011] In the step (1), the mass ratio of silica sol to ammonium polyphosphate is 1:3-2:3, the mass ratio of tubular kaolin to ammonium polyphosphate is 1:3-2:3, and the amount of ethanol used is 4-12 times the mass of ammonium polyphosphate.

[0012] In the step (2), the mass ratio of melamine to formaldehyde aqueous solution is 1:3-2:1, the mass ratio of ammonium polyphosphate to melamine-formaldehyde polymer is 3:1-3:2, the mass ratio of tubular kaolin to ammonium polyphosphate is 1:3-2:3, and the amount of ethanol used is 4-12 times the mass of ammonium polyphosphate.

[0013] In the step (3), the mass ratio of epoxy resin to ammonium polyphosphate is 1:5-1:2, the mass ratio of tubular kaolin to ammonium polyphosphate is 1:3-2:3, and the amount of ethanol used is 4-12 times the mass of ammonium polyphosphate.

[0014] In the step (3), the concentration of the formaldehyde aqueous solution is 20-40%, and the concentration of the triethanolamine aqueous solution is 5-20%; in the steps (2) and (3), the concentration of the hydrochloric acid is 5-20%.

[0015] In the step (1), the silica sol is added at a rate of 1-2 drops per second.

[0016] The tubular kaolin is tubular refractory kaolin, the average particle diameter of the tubular refractory kaolin particles is 0.2-2.0 μm, the inner diameter of the tubular refractory kaolin particles is 15-30 nm, the inner surface of the tubular refractory kaolin is rich in anionic and cationic groups, and has highly active reaction sites.

[0017] The tubular refractory kaolin is made of DRAGONITE produced by Japan FMT Co., Ltd. The internal structure of the tubular refractory kaolin contains abundant active anion and cation groups and has dense high-activity reaction points, which is conducive to the subsequent coating reaction. The tubular refractory kaolin has small particles, with an average particle diameter of 0.2-2.0μm and an inner diameter of 15-30nm, which is conducive to dispersion. In addition, it has good self-carbonization and auxiliary carbonization performance during high-temperature calcination.

[0018] The tubular kaolin modified ammonium polyphosphate functional monomer provided by the present invention is formed by organic-inorganic hybrid reaction of ammonium polyphosphate and tubular refractory kaolin, so that the advantages of the two are synergized to the greatest extent, its water resistance is significantly improved, and its carbonization effect and flame retardant efficiency are greatly improved, and it can be directly applied to the flame retardant of related materials. The reaction process of the present invention is simple, the raw materials are easily available, the operation is convenient and safe, and it is easy to promote and apply, and has good industrial promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the structure of tubular kaolin modified ammonium polyphosphate functional monomer. DETAILED DESCRIPTION

[0020] Example 1

[0021] Add 50g APP and 300ml ethanol into a 500ml three-necked flask and mix them. At a temperature of 50℃ and stirring, drop 25g silica sol into the three-necked flask at a dropping speed of 1-2 drops per second. After the dropping is completed, continue to keep warm for 2h. After the insulation reaction is completed, add 30g tubular kaolin into the three-necked flask, continue to stir and keep warm for 3-5h. After the reaction is completed, centrifuge to separate the solid and liquid, wash the obtained solid twice with anhydrous ethanol, and then dry it at a temperature of 60℃ to obtain a tubular kaolin modified ammonium polyphosphate functional monomer, recorded as APP-1.

[0022] Example 2

[0023] Take 20g of melamine and mix it with 40ml of 37% formaldehyde aqueous solution, adjust the pH to 7.5 with 10% triethanolamine aqueous solution, slowly heat it to 70℃ and keep it warm for 30min, after the reaction is completed, perform solid-liquid separation to obtain melamine-formaldehyde polymer; take 40g of APP and add it to 200ml of anhydrous ethanol to disperse evenly, adjust the pH to about 5 with 10% hydrochloric acid, slowly heat it to 78℃, first add 20g of melamine-formaldehyde polymer, keep the temperature at 78℃, continue stirring and react for 2h, then add 20g of tubular kaolin, continue to react at 78℃ and stirring for 4h, after the reaction is completed, centrifuge to separate the solid and liquid, wash the obtained solid twice with anhydrous ethanol, and then dry it at 60℃ to obtain tubular kaolin modified ammonium polyphosphate functional monomer, recorded as APP-2.

[0024] Example 3

[0025] Take 40g of APP and add it to 200ml of anhydrous ethanol and disperse it evenly. Adjust the pH to about 5 with 10% hydrochloric acid, slowly raise the temperature to 78°C, add 10g of epoxy resin, maintain the temperature at 78°C, continue stirring for 2h, then add 20g of tubular kaolin, continue stirring and keep warm for 4h. After the reaction is completed, centrifuge to separate the solid and liquid, wash the obtained solid twice with anhydrous ethanol, and then dry it at 60°C to obtain tubular kaolin modified ammonium polyphosphate functional monomer, recorded as APP-3.

[0026] In another aspect of the present invention, an environmentally friendly halogen-free fabric flame retardant coating adhesive is provided, which comprises the tubular kaolin-modified ammonium polyphosphate described in the present invention, which is compounded with other bromide-based or halogen-free flame retardants and acrylic emulsion.

[0027] Example 4

[0028] Bisphenol A-bis(diphenyl phosphate) (BDP for short), APP-1, brominated polystyrene, zinc borate, triazine carbon former (CFA), and epoxy resin were prepared in a mass ratio of 1.5:5.0:2.0:2.0:2.5:2.0 to obtain a mixture of 15.0 g of the above materials and added to a blending container. Then, 26 g of acrylic emulsion (emulsion solid content of 50%), 15 g of water, 0.5 g of emulsifier and 0.5 g of defoamer were added, and the mixture was stirred and dispersed evenly to obtain a flame retardant coating adhesive.

[0029] The flame retardant coating glue was scraped onto the back of the fabric (the fabric was white polyester cloth with a gram weight of 200g, i.e., the weight of each square meter of cloth was 200g), and baked (150°C, 180s) to obtain a low-smoke toxicity and high-efficiency flame retardant polyester sofa textile fabric (Sample 1) with a gram weight gain of 98.6g (i.e., the coating mass of each square meter of cloth was 98.6g).

[0030] Sample 1 was immersed in 500 ml of water at 45° C. for 30 min, dried and weighed to 93.7 g, and named as sample 1-1.

[0031] Example 5

[0032] The APP-1 in Example 4 was replaced by the Type II APP sold in the traditional market, and the rest remained unchanged. The coated fabric (Sample 2) had a gram weight gain of 99.8 g. Sample 2 was soaked in 500 ml of water at 45°C for 30 min, dried and weighed to 88.6 g, and named Sample 2-1.

[0033] Example 6: Bisphenol A-bis(diphenyl phosphate) (BDP for short), APP-2, melamine cyanurate, zinc borate, triazine carbonizing agent (CFA), and epoxy resin are mixed in a mass ratio of 1.5:5.0:2.0:2.0:2.5:2.0 to prepare a mixture of 15.0 g of the above materials and add the mixture to a blending container. Then, 26 g of acrylic emulsion (emulsion solid content is 50%), 15 g of water, 0.5 g of emulsifier and 0.5 g of defoaming agent are added, and the mixture is stirred and dispersed evenly to obtain a flame retardant coating adhesive.

[0034] The flame retardant coating glue was scraped onto the back of the fabric to obtain a low smoke toxicity and high efficiency flame retardant polyester sofa textile fabric (sample 3), with a gram weight gain of 100.2g. Sample 3 was soaked in 500ml water at 45℃ for 30min, dried and weighed to 95.2g, named sample 3-1.

[0035] Example 7

[0036] The APP-2 in Example 6 was replaced by the traditional Type II APP sold in the market, and the rest remained unchanged. The coated fabric (Sample 4) had a gram gain of 99.8 g. Sample 2 was soaked in 500 ml of water at 45°C for 30 min, dried and weighed to 89.1 g, and named Sample 4-1.

[0037] Example 8

[0038] Replace APP-2 in Example 6 with APP-3, and keep the rest unchanged. Coat the fabric (Sample 5) with a gram gain of 99.5 g. Soak Sample 5 in 500 ml of water at 45°C for 30 min, dry and weigh 93.9 g. Name Sample 5-1.

[0039] The flame retardant properties refer to the BS5852 flame retardant test standard. The soaked samples are covered with the specified polyurethane sponge and ignited under the specified burner. The butane flame height is 35mm. After the flame is stable for 30s, the flame is continuously burned for 20s to test the flame retardant properties of the sample. The test results are shown in Table 1.

[0040] Table 1

[0041] Flame retardant system type Sample Weight loss rate% Experimental phenomenon BS5852 Standard Bromine-Phosphorus Synergistic System (APP-1) 1-1 5.0 The fire will extinguish itself after 20 seconds. pass Bromine-phosphorus synergistic system (Type II APP) 2-1 11.2 After 15-18 seconds, the hole is broken and the flame does not go out Not passed Halogen-free flame retardant system (APP-2) 3-1 5.0 The fire will extinguish itself after 20 seconds. pass Halogen-free flame retardant system (Type II APP) 4-1 10.7 After 13-16 seconds, the hole is broken and the flame does not go out Not passed Halogen-free flame retardant system (APP-3) 5-1 5.6 The fire will extinguish itself after 20 seconds. pass

[0042] The water loss rate represents the water resistance of the flame retardant coating composition. The greater the water loss rate, the worse the water resistance of the flame retardant coating composition. As can be seen from the above table, the water resistance of APP modified by tubular kaolin is improved, and the water resistance of APP-II sold in the traditional market is poor.

[0043] From the results in Table 1 above, it can be seen that: Examples 5 and 7 use the traditional II-type APP on the market, but the mass loss after soaking in water is too large, and the flame retardant performance cannot reach the flame retardant standard of BS5852. Examples 4, 6, and 8 use the kaolin-modified APP of the present invention, which can reduce the loss of soaking in water, improve the water resistance, and improve the self-extinguishing effect of the product. It can reach the relevant flame retardant standard of BS5852.

[0044] The above is only a preferred embodiment of the present invention, and does not limit the technical solution of the present invention in any form. Any equivalent replacement or partial improvement made under the technical essence of the present invention will be regarded as within the protection scope of the present invention.

Claims

1. A tubular kaolin modified ammonium polyphosphate functional monomer, characterized in that: The functional monomer is prepared by embedding ammonium polyphosphate that has been subjected to nano-SiO2 grafting modification, epoxy coating modification or melamine coating modification into tubular kaolin; the functional monomer is prepared by the following steps (1), (2) or (3): (1) ammonium polyphosphate and ethanol are mixed evenly, and then silica sol is added dropwise at a temperature of 40-70°C under stirring. After the addition is completed, the reaction is continued for 2-5 hours. After the reaction is completed, tubular kaolin is added and the reaction is continued for 3-5 hours. After the reaction is completed, solid-liquid separation is performed. The separated solid is washed and dried to obtain tubular kaolin modified ammonium polyphosphate functional monomer; (2) Mixing melamine and formaldehyde aqueous solution, adjusting the pH to 7-9 with triethanolamine aqueous solution, heating to 60-85°C and reacting for 20-60 minutes, and performing solid-liquid separation after the reaction to obtain melamine-formaldehyde polymer; mixing ammonium polyphosphate and ethanol evenly, adjusting the pH to 4-6 with hydrochloric acid, heating to 70°C-80°C, adding melamine-formaldehyde polymer, keeping the temperature for reaction for 1.5-3h, then adding tubular kaolin, and continuing the keeping temperature for reaction for 3-5h. After the keeping temperature for reaction is completed, performing solid-liquid separation, and washing and drying the separated solid to obtain tubular kaolin modified ammonium polyphosphate functional monomer; (3) Mix ammonium polyphosphate and ethanol evenly and adjust the pH to 4-6 with hydrochloric acid, raise the temperature to 70°C-80°C, add epoxy resin, and keep the temperature for reaction for 1.5-3h; after the reaction is completed, add tubular kaolin, and continue to keep the temperature for reaction for 3-5h. After the reaction is completed, perform solid-liquid separation, and wash and dry the separated solid to obtain tubular kaolin modified ammonium polyphosphate functional monomer.

2. The tubular kaolin modified ammonium polyphosphate functional monomer according to claim 1, characterized in that: In the step (1), the mass ratio of silica sol to ammonium polyphosphate is 1:3-2:3, the mass ratio of tubular kaolin to ammonium polyphosphate is 1:3-2:3, and the amount of ethanol used is 4-12 times the mass of ammonium polyphosphate.

3. The tubular kaolin modified ammonium polyphosphate functional monomer according to claim 1, characterized in that: In the step (2), the mass ratio of melamine to formaldehyde aqueous solution is 1:3-2:1, the mass ratio of ammonium polyphosphate to melamine-formaldehyde polymer is 3:1-3:2, the mass ratio of tubular kaolin to ammonium polyphosphate is 1:3-2:3, and the amount of ethanol used is 4-12 times the mass of ammonium polyphosphate.

4. The tubular kaolin modified ammonium polyphosphate functional monomer according to claim 1, characterized in that: In the step (3), the mass ratio of epoxy resin to ammonium polyphosphate is 1:5-1:2, the mass ratio of tubular kaolin to ammonium polyphosphate is 1:3-2:3, and the amount of ethanol used is 4-12 times the mass of ammonium polyphosphate.

5. The tubular kaolin modified ammonium polyphosphate functional monomer according to claim 1, characterized in that: In the step (3), the concentration of the formaldehyde aqueous solution is 20-40%, and the concentration of the triethanolamine aqueous solution is 5-20%; in the steps (2) and (3), the concentration of the hydrochloric acid is 5-20%.

6. The tubular kaolin modified ammonium polyphosphate functional monomer according to claim 1, characterized in that: In the step (1), the silica sol is added at a rate of 1-2 drops per second.

7. The tubular kaolin modified ammonium polyphosphate functional monomer according to any one of claims 1 to 6, characterized in that: The tubular kaolin is tubular refractory kaolin, the average particle diameter of the tubular refractory kaolin particles is 0.2-2.0 μm, the inner diameter of the tubular refractory kaolin particles is 15-30 nm, the inner surface of the tubular refractory kaolin is rich in anionic and cationic groups, and has highly active reaction sites.